Conocimiento y presencia de hepatitis b en los estudiantes de pregrado de la Facultad de Odontología de la Universidad de Antioquia. 2003 - Hincapié-R., Alberto; Domínguez-O., Martha Cecilia; Garcés-J., Claudia Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2009)
At the present time, according to the Health World Organization reports, there is a high increase in the prevalence of infectious contagious diseases, in particular hepatitis B. Keeping in mind that health professionals are a group in high risk to acquire contagious diseases and that institutions that train health professionals have an important role in the future performance of their graduates it was considered pertinent to overtake a study that would evaluate the knowledge and presence of the hepatitis B virus —VHB— in the students and of the biological risk that they have in relation with their professional and social behavior. For this reason a descriptive transverse type of study was undertaken in 219 students from the sixth to the tenth semester of the College of Dentistry of the Universidad de Antioquia. The study allowed, with the methodology that was proposed, to identify that: there were no students who tested positive for the surface antigen of VHB; the vast majority (84,4%), have positive antibodies for VHB; the knowledge about hepatitis B and biosecurity is scarce and a representative group is exposed to contract HB according to their professional and social conducts.